Making critical decisions : - Snow, Roberta (Jossey-Bass, 2008)
Making Critical Decisions offers nonprofit leaders a proven model for making hard choices that minimize risks while maintaining progress toward the organization’s goals as well as a practical framework for understanding and implementing the decision-making process. The book includes qualitative and quantitative tools and offers illustrative case examples throughout that clearly show how this method can be applied to different types of nonprofit organizations